ETHICAL ASPECTS OF USING AI IN BUSINESS (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article is dedicated to the analysis of the ethical aspects of using artificial intelligence (AI) in business, examining how new technologies influence business practices and the moral, social, and legal issues arising during their implementation. In recent decades, AI has become an integral part of many business models, transforming industries and providing new opportunities for process optimization, productivity enhancement, and improved customer interactions. However, with its growing adoption, a number of ethical challenges emerge, necessitating attention and proper regulation.One of the central issues is the transparency of algorithms. AI systems often make decisions that are difficult to understand or explain, raising concerns about the opacity of their operations and the potential consequences for end-users. The article explores the importance of algorithmic explainability, which helps improve trust in AI systems from both businesses and consumers.The issue of fairness is also given considerable attention. AI can exacerbate bias if the data used to train models contains historical or social biases. This may lead to discrimination based on various attributes such as gender, age, or ethnicity. The article discusses approaches aimed at preventing such distortions in data and algorithms.Another significant topic is data protection and privacy. In the context of globalization and pervasive digitalization, personal data has become a valuable asset, and its leakage or misuse can result in serious legal and reputational consequences for companies. The article emphasizes the need to adhere to high standards of data security and comply with regulations such as the GDPR.Special attention is devoted to the impact of AI on workers. Automation and robotics may lead to significant changes in the labor market, creating the risk of job loss and deteriorating working conditions. The article analyzes potential solutions to this problem, such as worker retraining and the creation of new jobs in emerging fields.Accountability for decisions made by AI remains an important ethical issue. Who is responsible for errors or damage caused by automated systems? How should responsibility be distributed between developers, system owners, and the AI systems themselves? The article discusses various approaches to addressing this issue and proposes creating effective legal frameworks for regulating the use of AI in business.